2000
DOI: 10.1093/clinchem/46.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Automated Assay for HER-2/neu in Serum

Abstract: Background: The extracellular domain of the HER-2/neu oncogene product is increased in sera of some patients with epithelial cancers. Our aim was to develop an automated serum assay for the extracellular domain of the HER-2/neu protein. Methods: We used a monoclonal antibody labeled with fluorescein for capture and a monoclonal Fab′ fragment labeled with alkaline phosphatase for detection. Separation of bound and free detection conjugate was performed with magnetizable particles coated with mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In contrast to immunohistochemistry, serological HER-2/neu detection presented 23% of patients with serum concentrations exceeding the cut-off level of 15 ng/mL in the present study. The HER-2/neu Kit used in this study for serum diagnostics is tested in several studies and is accepted to be sensitive and specific, as well as to provide reproducible results (Payne et al 2000;Cook et al 2001;Carney et al 2003). HER-2/neu serum overexpression in ovarian cancer patients varies from 9% to 33% (Meden et al 1998;Cheung et al 1999;Bookman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to immunohistochemistry, serological HER-2/neu detection presented 23% of patients with serum concentrations exceeding the cut-off level of 15 ng/mL in the present study. The HER-2/neu Kit used in this study for serum diagnostics is tested in several studies and is accepted to be sensitive and specific, as well as to provide reproducible results (Payne et al 2000;Cook et al 2001;Carney et al 2003). HER-2/neu serum overexpression in ovarian cancer patients varies from 9% to 33% (Meden et al 1998;Cheung et al 1999;Bookman et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Payne et al have demonstrated that trastuzumab does not interfere with this serum HER2 assay. 16 The cutoff for this assay for normal and high sHER2 levels was 15 ng/mL according to the US Food and Drug Administration-approved ADVIA Centaur HER-2/neu assay recommendation. Of the total 3505 patients enrolled in the trial, baseline samples were available for 2318 patients participating in treatment arms A (n 5 795), B (n 5 814), and C (n 5 709).…”
Section: Methodsmentioning
confidence: 99%
“…The Bayer Immuno 1 HER2/neu assay is a magnetic particle separation immunoassay designed for the random access automated Bayer Immuno 1 immunochemistry analyzer (Bayer Diagnostics, Tarrytown, NY, USA). 17 Briefly, the assay uses a monoclonal antibody labeled with fluorescein for capture and a monoclonal Fab′ fragment labeled with alkaline phosphatase for detection. Separation of bound and free detection conjugate was performed with magnetizable particles coated with monoclonal antibody to fluorescein.…”
Section: Evaluation Of the Serum Her2 Levelmentioning
confidence: 99%